Role of Redox Signaling and Inflammation in Skeletal Muscle Adaptations to Training - Maria Carmen Gomez-Cabrera; Jose Viña; Li Li Ji (MDPI AG, 2016)
The inflammatory response to exercise-induced muscle damage has been extensively described. Exercise has important modulatory effects on immune function. These effects are mediated by diverse factors including pro-inflammatory cytokines, classical stress hormones, and hemodynamic effects leading to cell redistribution. As has been reported regarding oxidative stress, inflammation can have both detrimental and beneficial effects in skeletal muscle. In this review we will address the role of inflammation on protein metabolism in skeletal muscle. Specifically, we will review studies showing that treatment with cyclooxygenase-inhibiting drugs modulate the protein synthesis response to one bout of resistance exercise and to training. Understanding how these drugs work is important for the millions of individuals worldwide that consume them regularly. We will also discuss the importance of reactive oxygen species and inflammatory cytokines in muscle adaptations to exercise and the Janus faced of the use of antioxidant and anti-inflammatory drugs by athletes for optimizing their performance, especially during the periods in which muscle hypertrophy is expected.